Granger Causality Analysis of Shariah Banking Deposit to Conventional Banking Deposit - Isbandini Veterina (Indonesia Banking School, 2016)
Countries with a dual banking system always question the independence of Islamic Bank on conventional bank. Although theoretically there are basic differences between Islamic bank with its profit loss sharing principle and the conventional bank with its interest rate system, but still, is the return that Islamic banks give to their customer is purely based on the bank’s performance? There is always a question that the Islamic Bank system are benchmarking their return rate against the conventional Bank’s interest system. This research purpose is to test the independence of Islamic commercial bank from conventional commercial bank in Indonesia. This research is benchmarking to earlier research by Chong and Liu. The parameters being estimated are time deposit interest rate in conventional commercial bank in Indonesia and profit loss sharing rate in mudharabha time deposit in Islamic Commercial bank in Indonesia. Granger Causality Test is used to test if the time deposit interest rate affects the profit loss sharing rate and vice versa. This research shows that the interest rate of time deposit in conventional commercial bank in Indonesia doesn't effect the profit loss sharing rate in mudharabah time deposit in Islamic commercial bank. On the other hand, the profit loss sharing rate in mudharabah time deposit also doesn’t effect the interest rate of time deposit in conventional commercial bank in Indonesia.